Thermodynamic aspects of gasification derived syngas desulfurization, removal of hydrogen halides and regeneration of spent sorbents based on La2O3/La2O2CO3 and cerium oxides. (1st June 2017) - Svoboda, Karel; Leitner, Jindřich; Havlica, Jaromír; Hartman, Miloslav; Pohořelý, Michael; Brynda, Jiří; Šyc, Michal; Chyou, Yau-Pin; Chen, Po-Chuang
Graphical abstract: Highlights: Equilibrium concentrations of H2 S, COS, HCl and HF are computed for solid sorbents. The solid sorbents are based on pure solids: ZnO, cerium oxides, La2 O3 and La2 O2 CO3 . Interferences of HCl and HF in de-H2 S reactions are determined (T = 500–1100 K). Minimization of Gibbs free energy for the complex systems is used. Possibilities of La2 O2 S and Ce2 O2 S regenerations are assessed. Abstract: The thermodynamic analyses are focused on the determination of theoretical equilibrium concentrations of H2 S, HCl and HF for La2 O3, La2 O2 CO3 and Cex Oy -based sulfur compounds sorbents, on possible interferences of hydrogen halides in H2 S removal in the temperature range 600–1100 K and on upstream selective deep removal of HCl and HF in producer gas. Minimization of Gibbs energy for the system was used in more complicated situations. The lowest H2 S concentration (<0.1 ppm-v) can be attained by Ce2 O3 -based sorbents at temperatures below 800 K. Oxidation of the Ce2 O3 -based sorbents to less efficient higher Ce-oxides (with limit of CeO2 ) is thermodynamically preferred in real producer gas. Presence of CO2 in gas phase leads to formation of lanthanum oxy-carbonate (La2 O2 CO3 ) with lower efficiency in H2 S removal than La2 O3 . The thermodynamic analyses are also focused on suitable ways and conditions for regeneration of spent desulfurization sorbents (Ce2 O2 S and La2 O2 S) to the corresponding oxides or oxy-carbonates at temperatures 600 K–1100 K. The Ce2 O2 S-based spent cerium sorbents are advantageously regenerated by reaction with SO2 at temperatures over 700 K. In this way CeO2, elemental sulfur and small concentrations of S2 O are theoretically produced. If the cerium halides are formed, their decomposition and full Ce-sorbent regeneration is thermodynamically possible rather by reaction with steam. The La-based spent sulfur sorbents are restored by reaction with CO2 and H2 O vapor leading to formation of La2 O2 CO3 and H2 S. The suitable operating conditions involve temperatures between 700 and 800 K and higher operating pressures. Potential small contents of La-oxy-halides (LaOF and LaOCl) in the spent sorbent are converted into La2 O2 CO3 in such a regeneration process.